Impact of uncoordinated and coordinated charging of plug-in electric vehicles on substation transformer - Masoum, A.; Abu-Siada, Ahmed; Islam, Syed (Elixir, 2011)
With the rapidly growing interest in smart grid technology, plug-in electric vehicles (PEVs) are expected to become more popular as low emission replacement for the petroleum based vehicles. Significant PEVs charging activities will mostly take place in customer’s premises, public or corporate car parks and electric charging stations. Therefore, utilities are concern about the possible detrimental impacts of these sizeable and unpredictable loads on the performance of distribution grids. Based on a recently proposed real-time smart load management (RT-SLM) control strategy, this paper focuses on the impact of uncoordinated and coordinated PEVs charging on substation transformer loading, system losses and voltage profile. Detailed simulations are performed on a 449 node smart grid system consisting of the modified IEEE 23 kV distribution system serving 4 charging stations and 22 low voltage residential networks populated with PEVs.